2022
DOI: 10.3390/land11101623
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Promote Sustainable Regional Development and Biodiversity Conservation in Regions with Demographic Decline? The Case of UNESCO Biosphere Reserve Elbe River Landscape Brandenburg, Germany

Abstract: This paper analyzes the relationship between out-migration from rural areas, sustainable regional development and the conservation of biodiversity. Urbanization is a key challenge for sustainable development. Will the move to cities reduce land use pressures on rural areas, and thus provide opportunities for biodiversity conservation? This paper reviews the literature on the relationship between rural out-migration and biodiversity. Generalizing statements or even predictions are rarely possible, as regional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…However, the example of a peripheral biosphere reserve in Bavaria, Germany, demonstrates that local politicians place less emphasis on the biosphere reserve's contribution to economic development [67]. Research on policy diffusion through governmental channels has shown two typical outcomes: the policy is either adopted in a copy-and-paste manner or adapted to suit local conditions [68].…”
Section: Discussionmentioning
confidence: 99%
“…However, the example of a peripheral biosphere reserve in Bavaria, Germany, demonstrates that local politicians place less emphasis on the biosphere reserve's contribution to economic development [67]. Research on policy diffusion through governmental channels has shown two typical outcomes: the policy is either adopted in a copy-and-paste manner or adapted to suit local conditions [68].…”
Section: Discussionmentioning
confidence: 99%